Pembuatan Perpustakaan Mini Guna MeningkatkanMinat Baca Anak Di Desa Buana Bhakti - Wahyu Hamidi; Adinda Cantika; Amanda Permata Sari; Annisa Syafawani; Abdul Latif; Herick Fernandez; Muhammad Nas Qori; Nasywa Loran Armelin; Nadila Julian; Verdiansyah Verdiansyah; Yingsih Safma Putri (FKIP, Universitas Palangka Raya, 2023)
One of the problems that exists in the community of Buana Bhakti Village, Kerinci Kanan District, Siak Regency nowadays is the lack of interest in reading. One of the programs implemented in Buana Bhakti Village is the creation of a mini library. The aim of creating a mini library is to help the community, especially children, develop a love for the culture of interest in reading, increase learning experiences other than in the classroom and also as a center for community empowerment to develop literacy-based potential. The result of this program is that children are enthusiastic about visiting the library to study and read.